Study of Thitonia Diversifolia Extract in Histomorphology of Pancreas and Interleukin-1beta expression on Aloxan Induced Wistar Rats - Rondius Solfaine; lailatul muniroh; iwan sahrial hamid (Jurnal Sain Veteriner, 2022)
The purpose of this study is to determine effect of antiinflammation of Thitonia diversifolia (TD) extracts in histopathology liver and pancretic tissue on alloxan-induced in Wistar rat. Thirty two male Wistar rats (Rattus norvegicus) with a body weight (bw)150-200 g in 3 month of age, were allocated into four groups, with eight animals per group. The control group received normal saline (P0), positive control group  received CMC Na 0.01% (P1),  the treatment group were received 100 mg/kg bw of the TD extracts (P2) and received 100 mg/kg bw of the metformin (P3)  respectively for 7 days. Bloods serum collected for measuring of  blood glucose (BG). cholesterol and insulin (INS) concentrations. The levels of insulin (INS) concentrations were analysed by Avidin-Horseradish Peroxidase (HRP) Sandwich-ELISA. All animal were sacrified for tissue staining with haematoxylin eosin. Thitonia diversifolia extract significantly decreased the level of blood glucoseand choelsterol concentrations compared to the postive control group (p<0.05). The level of INS could be detected by its level significantly increased in TD treatment group (p<0.05). Histopathological showed that induction of alloxan could effect severe multifocal degeneration, vacuolisation, cell inflammation, acute langerhan cells injury with destruction cells. Immunohistochemical staining labeled with IL-1β monoclonal antibodies (Mab) showed lowering expression of IL-1β reveal as brownish color aggregates on the langerhans cells in the TD treatment group. This study was concluded that TD extract is inhibited hepatic tissue injuries and decreased destruction in langerhan cells by decreasing IL-1β expression on alloxan-induced rats.